Biological efficacy of low against medium dose aspirin regimen after coronary surgery: Analysis of platelet function - Cornelissen, Jacqueline; Kirtland, Stephen; Lim, Eric; Goddard, Martin; Bellm, Sarah; Sheridan, Kate; Large, Stephen; Vuylsteke, Alain (Thrombosis and Haemostasis, 2006)
The failure of aspirin to inhibit platelet function has been documented in patients undergoing coronary artery bypass graft (CABG) surgery, but the causes of “aspirin-resistance” remain uncertain. The aim of this study was to investigate the efficacy of aspirin in patients undergoing CABG surgery receiving either 100 mg or 325 mg of oral aspirin for 5-days.Platelet function was tested the day before surgery and on day+1 and day+5, and evaluated by changes in collagen-induced thromboxane-A2 (TxA2) release and platelet aggregation following stimulation with collagen, ADP and epinephrine. In all patients, baseline platelet aggregation was significantly inhibited by pre-incubation with in vitro aspirin (150 µmol/l), with a mean reduction in TxA2-release of ≥95.5% (82.3, 99.1). After 5-days of oral aspirin, platelet aggregation was significantly inhibited, and was not further inhibited by in vitro aspirin. Oral aspirin was also associated with a ≥99.5% (97.8, 99.7) reduction in TxA2-release, and with the reversal of the second-phase of ADP-induced aggregation which is TxA2-dependent. In addition a single-dose of 325mg aspirin on the first post-operative morning may have a greater inhibitory effect on collagen-induced aggregation than 100mg aspirin. Western blot analysis provided no evidence for the presence of COX-2 in platelets, while the up-regulation of p38-MAPK following platelet-stimulation and surgery was seen. The inhibition of COX-2 (NS398) or p38-MAPK (SB203580) activity did not affect platelet aggregation and TxA2-release on day+5. In summary, there was no evidence for inherent or acquired aspirin-resistance in this surgical population, or for the involvement of either COX-2 or p38-MAPK.
Keywords: CABG surgery; aspirin; platelets; thromboxane A2